2019
DOI: 10.1111/ibi.12799
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal movement of the Bearded Vulture using GPS telemetry in the Himalayas of Nepal

Abstract: This study addresses for the first time the movement patterns of the globally near‐threatened Bearded Vulture Gypaetus barbatus in its most important stronghold, the high‐altitude mountain ranges of Asia. Tracked individuals (n = 8) in the Annapurna Himalayan range (Nepal) foraged over a vast range of 60 715.9 km2 and our results indicated age‐class differences in the use of space. Territorial adults showed very small annual home‐ranges (K90 = 150.3 km2), whereas immatures wandered extensively and covered vast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…If the repeated GPS locations were obtained from the same place, the site was visited for ground truthing and causes were recorded (e.g. mortality or failure of GPS unit; see details in Subedi et al 2020).…”
Section: Gps-tracking Raptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the repeated GPS locations were obtained from the same place, the site was visited for ground truthing and causes were recorded (e.g. mortality or failure of GPS unit; see details in Subedi et al 2020).…”
Section: Gps-tracking Raptorsmentioning
confidence: 99%
“…the Himalayan range and adjacent areas, raptors are perceived to be predators of domestic fowl and other game animals (Pohja-Mykrä et al 2012, Madden et al 2019. Ranging data provided by GPS-tracked Bearded Vulture (11 birds) suggested that about 70% of their home range remains outside protected areas in Nepal and in humandominated areas (Subedi et al 2020), and 48% of the home range area of Mountain Hawk Eagle (three birds) remains within agriculture areas. Ranging data indicated these raptors are highly associated with human-dominated landscapes, and this is likely to increase the risk of human persecution, such as the killing of a few individuals as a revenge for predating domestic fowl (e.g.…”
Section: Human Persecutionmentioning
confidence: 99%
“…Unlike badgers and other terrestrially moving animals, vultures can move great distances with minimal obstruction [Figure 11]. Vultures can also move greater distances more rapidly, 95 resulting in a more variable and distribution of step lengths [96][97][98] [Figure 10].…”
Section: Ecology and Objectives -Vulturementioning
confidence: 99%
“…Medium site fidelity via the use of multiple roosting/resting sites 99 2. Movement speed approximated by summary statistics from previous studies, [95][96][97][98] with minimal landscape derived resistance 3. A 8-12 hour activity cycle, 100 that shifts over the year 95,96,101 Figure 11.…”
Section: Ecology and Objectives -Vulturementioning
confidence: 99%